(untitled) (Bangladesh Medical Journal, 2012)
We are reporting a case of morbid obesity with related complications. This unfortunate 32 years old poor gentleman has been suffering from morbid obesity since his early childhood and presented to us with palpitation, shortness of breadth on exertion and chest pain, difficulty in micturation for the last 8 year Clinically the patient has been diagnosed as a case of Morbid Obesity with Left Ventricular Hypertrophy & Heart Failure, with Diabetes Mellitus, and Urethral Stricture. After meticulous search for all secondary causes of morbid obesity the reason for his obesity was considered as Genetic. DOI: http://dx.doi.org/10.3329/bmj.v39i3.9949 BMJ 2010; 39(3)